Outcome-based Approach in Development of a Disaster Management Course for Healthcare Workers - Wickramasinghe, Kremlin Khamarj; Ishara, Mohamed Hassim; Liyanage, P.; Karunathilake, I.M.; Samarasekera, Dujeepa (My University, 2007)
Introduction: The Faculty of Medicine, University of Colombo, Sri Lanka provided voluntary healthcare services during the aftermath of the 2004 tsunami. At that time the faculty recognised the need to prepare the healthcare system for future disasters by enhancing the capability of healthcare workers. The development and implementation of a disaster management course for healthcare workers was identified as a priority. Method: An outcome-based approach was used to develop the curriculum. Qualitative and quantitative methods were used to identify the core competencies and outcomes that healthcare workers need to achieve at the end of the course. The content, teaching learning methods and assessments were aligned with the course outcomes. The course consists of 9 core modules and an elective research module. Formative and summative assessment methods were included. Conclusion: Training is an important component of disaster management. The outcome-based approach provides a useful framework for developing such training programmes and ensures that needs are addressed.